Conditions for supply chain management: Case of the tobacco industry in Honduras (Journal of Management & Business, 2021)
In this research, the supply chain is approached as a functional process for organizations in terms of its operability and how they generate value through their processes. Its objective is to measure the conditions for the efficient management of the supply chain in the tobacco industry in Honduras. The methodology is exploratory and descriptive; A 3-level Likert-type measurement scale was applied. The scale was applied to 91 employees of the 13 factories registered with the Association of Tobacco Producers in Honduras (Aprotabacoh). In the results, it was found that there is a correlation between the study variables and the weightings of the statistical analysis of the reagents, concluding in the verification of the hypotheses that all were accepted, establishing an adequate measurement of the supply chain that contribute to the operation of the industries. tobacco processors in Honduras.
Keywords: Management; efficiency; supply chain; tobacco